Pengaruh Servicescape dan Kualitas Pelayanan Frontliner terhadap Kepuasan Nasabah Bank Pembiayaan Rakyat Syariah Amanah Bangsa Sidamanik - Putri Shakinah; Mustafa Kamal Rokan; M. Ikhsan Harahap (Universitas 45 Surabaya, 2024)
The aim of this research is to determine the influence of servicescape and frontline service quality on customer satisfaction at Amanah Bangsa Sidamanik Sharia People's Financing Bank. This research uses quantitative research. In this research, a questionnaire was used to collect data, and 100 customers of the Amanah Bangsa Sidamanik Sharia People's Financing Bank were selected as samples using a simple random sampling method. Data analysis in this research is quantitative data analysis. Statistical tests known as Multiple Linear Regression Tests, T-tests, F-tests, and Coefficient of Determination (R2) are all components of this analysis, as well as the Classical Assumption Test. Based on hypothesis testing with the partial T test, it can be concluded that the Servicescape and Frontliner Service Quality variables partially have a significant effect on customer satisfaction. Based on simultaneous F test hypothesis testing, it can be concluded that the servicescape and frontline service quality variables together influence BPRS Amanah Bangsa customer satisfaction.